Neoboutonia melleri var velutina Prain: in vitro and in vivo hepatoprotective effects of the aqueous stem bark extract on acute hepatitis models - Anne Marie Endougou Effa; Emilie Gantier; Thierry Hennebelle; Vincent Roumy; Céline Rivière; Théophile Dimo; Pierre Kamtchouing; Pierre Desreumaux; Laurent Dubuquoy (BMC, 2018)
Abstract Background Hepatitis is a liver inflammation caused by different agents and remains a public health problem worldwide. Medicinal plants are an important source of new molecules being considered for treatment of this disease. Our work aims at evaluating the hepatoprotective properties of Neoboutonia velutina, a Cameroonian medicinal plant. Methods The aqueous extract has been prepared using phytochemical methods. HepG2 cells were used to assess anti-inflammatory properties of the extract at different concentrations. Acute hepatitis models (Carbon tetrachloride and Concanavalin A) were performed in mice receiving or not receiving, different extract doses by gavage. Liver injury was assessed using histology, transaminases and pro-inflammatory markers. Extract antioxidant and radical scavenging capacities were evaluated. Results The extract led to a significant decrease in pro-inflammatory cytokine expression in vitro and to a remarkable protection of mice from carbon tetrachloride-induced liver injury, as shown by a significant decrease in dose-dependent transaminases level. Upon extract treatment, inflammatory markers were significantly decreased and liver injuries were limited as well. In the Concanavalin A model, the extract displayed weak effects. Conclusions Taking into account underlying mechanisms in both hepatitis models, we demonstrate the extract's radical scavenging capacity. Neoboutonia velutina displays a potent hepatoprotective effect mediated through radical scavenging properties.